Leveraging Artificial Intelligence to Enhance Employment Opportunities for Individuals with Sickle Cell Disease in Telangana and Andhra Pradesh - Shaheen, Umaiza Sadia (Journal of Informatics Education and Research, 2025)
Sickle Cell Disease (SCD) is a global health challenge, especially in sub-Saharan Africa, the Middle East, and parts of India. In India, SCD is endemic among tribal populations, with over 20 million carriers and 1.5 million affected individuals, and states like Maharashtra, Gujrat, Odisha, and Chhattisgarh report high prevalence. Similarly, in Telangana, it is widespread among tribal communities, particularly in districts like Adilabad and Khammam, significantly impacting individuals’ quality of life, and creating barriers in acquiring sustainable employment. This study aims to explore the specific employment challenges faced by individuals with SCD in the states of Telangana and Andhra Pradesh, focusing on factors such as literacy, physical limitations, pain crises, stigma, access to supportive technologies, and the lack of workplace accommodations. It will also assess how SCD influences career choices, job performance, and the ability to maintain steady employment. Additionally, it investigates the potential of Artificial Intelligence (AI)-driven solutions, such as remote work, flexible work arrangements, and AI-powered tools for task automation and health monitoring, to address these challenges. By examining the feasibility and effectiveness of AI in providing tailored support, the study aims to identify opportunities for improving employment prospects and job stability for individuals with SCD. The findings will provide actionable recommendations for employers, policymakers, and healthcare providers to create inclusive and supportive work environments, leveraging AI to enhance work-life balance, reduce health-related barriers, and empower individuals with SCD to pursue and retain fulfilling careers while managing their health.